Reproductive Biology of Puntioplites bulu Blkr from the BatangMahat River, Kampar Regency, Riau Province - Salmah Lismarinda Cibro; Windarti Windarti; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractPuntioplites bulu is a type of freshwater fish that commonly inhabit the Batang Mahat River, Riau. A study aims to understand the reproductive biology of P. bulu has been conducted. The fish was sampled 6 times, second/month, from January to March 2019. Parameters measured were sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter. Results shown that there were 31 males and 34 females (sex ratio 1:1). The male has slimmer body and brighter color than those of the female. The gonadal matury levels in females was 3 in Batang Mahat River. The average GSI of fish ranged from 0.26-3.78%. The average fecundity of the female was 179.12-202.57. Egg diameter ranged from 0.66-1.20 mm, where the small egg (0.66-0.92 mm) was 83-84%, the medium egg (0.93-1.19) was 14-15% and the large egg >1,20 was 1.67%. Based on the size of egg diameter can be concluded this fish is total spawner.Keywords: Sex ratio, gonad matury level, gonad somatic index, fecundity Total spawner